The New Trend in the EU’s Migration Policy: Is Externalization Any Better? - Vasil Pavlov; Raquel Cardoso (Journal of Liberty and International Affairs)
The highly dynamic security environment, characterized by numerous disturbances such as armed conflicts, civil wars, and political and social instability in various parts of the world, has led millions of people to flee their countries of origin – as of 2023, this number is 117,3 million. Against this background, the EU’s migration policy has shifted from predominantly “open-door” during the 2014-2016 migration inflows to more restrictive measures to secure external borders. Part of these actions were the agreements with third countries as an alternative to effectively combatting irregular immigration. This paper aims to identify gaps in these EU agreements and suggest a more comprehensive approach. Comparative analysis, documentary analysis, and statistical data analysis were used in this respect